The Correlation Between Physical Activity and Kidney Stone Formation: A Literature Review - Hernawan, Budi; Gonzales, Nico (Smart Medical Journal, 2023)
Background: Kidney stones or nephrolithiasis is a disease where crystals form in kidney due to increased excretion of stones-forming components such as calcium, oxalate, uric acid, cystine, xanthine, and phosphate, or reduced urine volume. In addition, poor eating and drinking habits along with lack of physical activity put individuals at a high risk of developing kidney stones. Previous studies showed that physical activity can both reduce and increase the risk of kidney stones.Purpose: This study aims to determine the relationship between physical activity and formation of kidney stones.Method: A literature review design was used by conducting a journal search through PubMed, Science Direct, and Google Scholar databases using the keywords ("kidney stone" OR nephrolithiasis OR urolithiasis OR "renal calculi") AND ("physical activity" OR exercise)".Results: The results showed a total of 15 articles that discussed correlation between physical activity and kidney stones formation. Ten articles explained that physical activity reduced kidney stones formation, while four reported no significant effect. The last article stated that physical activity increased kidney stones formation Conclusion: Kidney stones formation occurred through the exacerbation of hypercalciuria in the absence of physical activity. Moderate physical activity reduced formation of kidney stones by decreasing calcium excretion in the urine. Meanwhile, excessive physical activity increased the occurrence of kidney stones in the absence of adequate fluid intake.